El predicador Andrés Ferrer de Valdecebro sueña con unicornios americanos (Revista de Crítica Literaria Latinoamericana, 2025)
The essay focuses on the intersection between the art of preaching and Creole identity in the 17th-century Hispanic World. I study the life and works of Andrés Ferrer de Valdecebro, a Dominican priest who was born in Spain and lived in Mexico for more than ten years. Specifically, I will analyze the way in which this author reflects on the connections between the practices of preaching and the foundation of a Creole imaginary. I will demonstrate how this plural, heterogeneous, and polyphonic process that we now know as the creation of a Creole view developed from multiple and unstable discursive positions.
Keywords: Andrés Ferrer de Valdecebro; Preaching; Creole identity; Puebla; Transatlantic imaginary; Intellectual community